2020
DOI: 10.1200/jco.2020.38.15_suppl.5012
|View full text |Cite
|
Sign up to set email alerts
|

DUTRENEO Trial: A randomized phase II trial of DUrvalumab and TREmelimumab versus chemotherapy as a NEOadjuvant approach to muscle-invasive urothelial bladder cancer (MIBC) patients (pts) prospectively selected by an interferon (INF)-gamma immune signature.

Abstract: 5012 Background: Cisplatin-based neoadjuvant chemotherapy (CT) followed by radical cystectomy (RC) is a standard treatment for MIBC. PD-1/L1 inhibitors as single agent induce pathological complete responses (pCR) in this setting. Predictors of response are still ill defined. DUTRENEO trial aimed to prospectively explore the activity of anti-PDL1 + anti-CTLA4 vs CT in pts selected according to a tumor pro-inflammatory IFN-gamma signature (tumor immune score, TIS). Methods: Cisplatin-eligible pts with urothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 0 publications
0
37
0
4
Order By: Relevance
“…In contrast to studies with anti-PD1/PD-L1 monotherapy, complete response to ipilimumab plus nivolumab in the NABUCCO trial was independent of baseline CD8 + presence or T-effector signatures [32]. However, recent results from the randomized phase II DUTRENEO trial did not demonstrate enhanced antitumor efficacy in selected patients treated with the combination durvalumab + tremelimumab on the basis of tumor inflammation signature (ie, 18 genes) [37]. Second, PD-L1-positive status evaluated as a CPS correlated separately with pCR in patients who received preoperative pembrolizumab.…”
Section: Predictors Of Response To Icb In the Neoadjuvant Settingmentioning
confidence: 81%
“…In contrast to studies with anti-PD1/PD-L1 monotherapy, complete response to ipilimumab plus nivolumab in the NABUCCO trial was independent of baseline CD8 + presence or T-effector signatures [32]. However, recent results from the randomized phase II DUTRENEO trial did not demonstrate enhanced antitumor efficacy in selected patients treated with the combination durvalumab + tremelimumab on the basis of tumor inflammation signature (ie, 18 genes) [37]. Second, PD-L1-positive status evaluated as a CPS correlated separately with pCR in patients who received preoperative pembrolizumab.…”
Section: Predictors Of Response To Icb In the Neoadjuvant Settingmentioning
confidence: 81%
“…While The PURE-01 trial reported that pembrolizumab was associated with a 37% complete response (pT0) after neoadjuvant therapy, the ABACUS trial showed that atezolizumab yielded a complete response rate of 31%. Conversely, preoperative combination of ipilimumab + nivolumab ( 18 ), cisplatin plus gemcitabine plus pembrolizumab ( 19 ), durvalumab + tremelimumab ( 20 ), was associated with a complete pathologic response rate of 46%, 44, 34.8%, respectively. Combination of 4 cycles of cisplatin-gemcitabine plus 4 cycles of nivolumab in the BLASST-1 trial was able to yield a complete pathologic response rate in 20 of 41 of patients or 49% of patients ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab is also being tested in a randomized phase III trial as adjuvant therapy after radical surgery in patients with muscle-invasive (node-positive) urothelial carcinoma. This trial, AMBASSADOR, is enrolling patients with ≥ypT2 disease and/or nodal involvement at radical surgery after neoadjuvant chemotherapy, or ≥ypT3 disease after no neoadjuvant chemotherapy and 91 However, all other monotherapy and combination studies in table 4 did not identify a significant response correlation with tumor or IC PD-L1 status.…”
Section: Panel Recommendationsmentioning
confidence: 99%